Bias-Induced Optical Absorption of Current Carrying Two-Orbital Quantum Dot with Strong Electron-Phonon Interaction (Polaron Regime) - A. Eskandari-asl (Journal of Sciences, Islamic Republic of Iran)
The one photon absorption (OPA) cross section of a current carrying two-orbital quantum dot (QD) with strong electron-phonon interaction (polaron regime) is considered. Using the self-consistent non-equilibrium Hartree-Fock (HF) approximation, we determine the dependence of OPA cross section on the applied bias voltage, the strength of effective electron-electron interaction, and level spacing of QD. Our numerical results reveal a unique property that there are two distinct regimes for OPA. We find that for values of level spacing of QD smaller than half the strength of effective electron-electron interaction and all values of applied bias voltage, the absorption is due to the excitation of the plasmon modes of the system with low cross section, but for the values of level spacing larger than the aforementioned value, within a finite range of the applied bias voltage, set by the values of level spacing and the strength of electron-electron interaction, the OPA is due to electron transition between the two orbitals of QD with an order of magnitude larger cross section than the former case. This property results in an almost square shape cross section as a function of applied bias, for peak values of absorption at resonance frequencies.